The Comparison of Civil Procedure and Industrial Relations Courtprocedure - PN, Sugeng Santoso (Halu Oleo University, 2019)
The Industrial relations dispute which is resolved through the Industrial Relations Court puts the workers/laborers against the employers and bases their formal source of law on the Article 57 of Law No. 2/2004 which basically uses the civil procedure except under special regulation. The analysis in this study shows that the implementation of civil procedure actually contravenes the labor law. The characteristics of the Industrial Relations Court procedure differs from the civil procedure.